Welding performance of a homemade friction stir welding tool - Hilmy, Irfan; Adesta, Erry Yulian Triblas (Trans Tech Publications Ltd., Switzerland, 2014)
Homemade Friction Stir Welding (FSW) Tool utilizing conventional milling machine has been developed. The FSW tool made from mild steel was designed and fabricated. Experimental investigation of FSW process of the Aluminum alloy specimens to observe its mechanical performances was performed. To evaluate its performance, hardness test, tensile test as well as visual inspections of the welding result were performed. Hardness number in the welding region was measured about 40-60% lower than the base metal, and heat affected zone region. The tensile test result varies with maximum 100 MPa. The imperfection of final form of metal due to the stirring mechanism was inspected. The presence of void/crack at cross-section of the welded specimen was observed. It was found that by applying suitable configuration, the use of mild steel as the FSW tool was reasonable for performing FSW process. It was concluded that, using a relatively low cost FSW tool, a quite satisfactory result of welding performance was achieved.